The effects of sucrose and arsenic on muscular insulin signaling pathways differ between the gastrocnemius and quadriceps muscles - Pánico, Pablo; Velasco, Myrian; Salazar, Ana María; Ostrosky-Wegman, Patricia; Hiriart, Marcia (Frontiers in Endocrinology, 2023)
Background: Insulin resistance in muscle can originate from a sedentary lifestyle, hypercaloric diets or, the exposure to endocrine-disrupting pollutants such as arsenic. In skeletal muscle, insulin stimulates glucose uptake by translocating GLUT4 to the sarcolemma. This study aimed to evaluate the alterations induced by sucrose and arsenic exposure in vivo on the pathways involved in insulin-stimulated GLUT4 translocation in the quadriceps and gastrocnemius muscles. Methods: Male Wistar rats were treated with 20 % sucrose (S), 50 ppm sodium arsenite (A) or both (A+S) in drinking water for 8 weeks. We made an intraperitoneal insulin tolerance (ITT) test on the seventh week of treatment. Quadriceps and gastrocnemius muscles were obtained after overnight fasting or after 30 min of intraperitoneal insulin injection. We assessed changes in GLUT4 translocation to the sarcolemma by cell fractionation and abundance of the proteins involved in GLUT4 translocation by Western blot. Results: Male rats consuming S and A+S gained more weight than control and A-treated animals. Rats consuming S, A, and A+S developed insulin resistance assessed through ITT. Neither treatments nor insulin stimulation in the quadriceps produced changes in GLUT4 levels in sarcolemma and Akt phosphorylation. Conversely, A and A+S decreased protein expression of Tether containing Ubx domain for GLUT4 (TUG), and A alone increased calpain-10 expression. All treatments reduced this muscle's protein levels of VAMP2. Conversely, S and A-treatment increased basal GLUT4 levels in the sarcolemma of the gastrocnemius, while all treatments inhibited insulin-induced GLUT4 translocation. These effects correlated with lower basal levels of TUG and impaired insulin-stimulated TUG proteolysis. Moreover, animals treated with S had reduced calpain-10 protein levels in this muscle, while A and A+S inhibited insulin-induced Akt phosphorylation. Conclusion: Arsenic and sucrose act through different pathways to impair GLUT4 trafficking, and the effects differ between the quadriceps and gastrocnemius.